PROSPEK USAHA PEMBESARAN IKAN MAS (Cyprinus carpio) PADA KOLAM DI DESA MOMPANG JULU KECAMATAN PENYABUNGAN UTARA KABUPATEN MANDAILING NATAL - Marlina Hotma; Zulkarnaini '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on April 2016 in Mompang Julu Village Penyabungan Utara Subdistrict, Mandailing Natal Regency. The puspose of this study was to know investment cost, gross income, nett income, feasibility and prospect of enlargement cultivation of carp in pond on the future. This study used a survey method. The population in this study is the fish farmers. The respondent determined by census. Based on the result of this study concluded that the, financial analysis and the feasibility is Rp. 48.167.100 investment cost, Rp. 55.843.200 gross income, Rp. 17.154.000 nett income, 1,39 BCR and 39,68 FRR. So, it can be a conclution that, the rear fish farming business prospect was profitable and feasible to develop. Keywords : Enlargement Carp, Pond, Investment, gross income, nett income, feasibility